PENGARUH SIMPANAN SAHAM TERHADAP KETAHANAN LEMBAGA DENGAN JUMLAH ANGGOTA SEBAGAI VARIABEL MODERASI PADA KSP. KOPDIT BINA PERTIWI MAUMERE - Angelucia Cindy Sulistiawati (CV. Denasya Smart Publisher, 2026)
This study aims to examine and analyze the effect of share savings on institutional resilience, with the number of members as a moderating variable at KSP Kopdit Bina Pertiwi Maumere. This research employs a quantitative approach. The data used are financial reports consisting of share savings, number of members, and the cooperative’s net income (Sisa Hasil Usaha/SHU) from fiscal years 2020 to 2024. The analytical methods applied include simple linear regression and Moderated Regression Analysis (MRA). The results indicate that share savings do not significantly affect institutional resilience, meaning that the amount of share savings does not directly increase the cooperative’s profit or resilience. Furthermore, the number of members does not moderate the relationship between share savings and institutional resilience. This suggests that even when membership declines, it does not necessarily enhance the contribution of share savings to SHU growth. The contribution of this study is to provide empirical insights for developing more effective cooperative governance strategies aimed at improving community economic welfare through the optimization of financial structure and membership engagement.